Surgical oncology in the age of multimodality therapy for cancer of the upper and lower gastrointestinal tract. Issue 5 (4th May 2021) - Neumann, Philipp-Alexander; Berlet, Maximilian Wolfgang; Friess, Helmut
ABSTRACT: Introduction: To date, all efforts to fight gastrointestinal cancer, regardless of its origin and entity, have resulted in complex therapeutic regimens involving a combination of systemic therapy, radiation therapy and surgery. It is generally accepted across all disciplines that not one, but the combination and the proper timing of all modalities result in the best oncologic outcome. Areas covered: Here, we provide insight into the current and future value of multimodal therapeutic approaches for upper and lower gastrointestinal cancer. Various aspects of treatment as well as open questions regarding indication and timing of multimodal strategies are addressed in this review. Expert opinion: In order to further improve the survival and quality of life of patients with gastrointestinal tumors in the future, scientifically proven multimodal therapy concepts are needed first and foremost. In addition, markers are pivotal to assign individual patients to a specific concept and to monitor the success of therapy. The main question is in which situation a neoadjuvant, perioperative or adjuvant radio-, chemo- or immunotherapy is superior. In fact, almost every curatively intended concept still contains surgical resection. Thus, improvement in surgical technique is also critical for multimodality concepts.